Cross sectional Evaluation of Adverse Drug Reactions Associated with Perioperative Medications in Surgical Patients - Dr Namrata Balaraddiyavar, Dr Sanjeev Kakaraddi, Dr Deepak Kurahatti (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Perioperative medications are essential for anaesthesia, infection prevention, paincontrol, haemodynamic stability and postoperative recovery. However, the simultaneousadministration of multiple drugs may increase the risk of adverse drug reactions, ranging frommild nausea and allergic manifestations to serious cardiovascular or respiratory complications. Systematic evaluation of perioperative ADRs is important for identifying high-risk medications, preventable factors and vulnerable patient groups